Peripheral Blood Stem Cell Mobilization in Healthy Donors by Granulocyte Colony-Stimulating Factor Causes Preferential Mobilization of Lymphocyte Subsets - Melve, Guro Kristin; Ersvaer, Elisabeth; Eide, Geir Egil; Kristoffersen, Einar K.; Bruserud, Øystein (Frontiers in Immunology, 2018)
Background: Allogeneic hematopoietic stem cell transplantation is associated with a high risk of immune-mediated post-transplant complications. Graft depletion of immunocompetent cell subsets is regarded as a possible strategy to reduce this risk without reducing antileukemic immune reactivity. Study design and methods: We investigated the effect of hematopoietic stem cell mobilization with granulocyte colony-stimulating factor (G-CSF) on peripheral blood and stem cell graft levels of various T, B and NK cell subsets in healthy donors. The results from flow cytometric cell quantification were examined by bioinformatics analyses. Results: The G-CSF induced mobilization of lymphocytes was a nonrandom process with preferential mobilization of naïve CD4+ and CD8+ T cells together with TCRɑβ+ T cells, naïve T regulatory cells, type 1 T regulatory cells (Tr1), mature and memory B cells and cytokine-producing NK cells. Analysis of circulating lymphoid cell capacity to release various cytokines (IFNɣ, IL10, TGFβ, IL4, IL9, IL17 and IL22) showed preferential mobilization of IL10 releasing CD4+ T cells and CD3-19- NK cells. During G-CSF treatment the healthy donors formed two subsets with generally strong and weaker mobilization of immunocompetent cells, respectively; hence the donors differed in their G-CSF responsiveness with regard to mobilization of immunocompetent cells. The different responsiveness was not reflected in the graft levels of various immunocompetent cell subsets. Furthermore, differences donor G-CSF responsiveness was associated with time until platelet engraftment. Finally, strong G-CSF induced mobilization of various T cell subsets seemed to increase the risk of recipient acute graft versus host disease (GVHD), and this was independent of the graft T cell levels. Conclusion: Healthy donors differ in their G-CSF responsiveness and preferential mobilization of immunocompetent cells. This difference seems to influence post-transplant recipient outcomes.